Fabrication of polymeric composite nanofiber materials and their antibacterial activity for effective wound healing - More, Dikeledi Selinah (Vaal University of Technology, 2023)
The synthesis of Ag and Cu nanoparticles was carried out using the thermal decomposition method in the presence of oleylamine as a capping agent. This method was used because it can produce uniform and monodisperse nanoparticles with controlled size distribution. The nanoparticles synthesized under various conditions were characterized by transmission electron microscopy (TEM), UV/Vis spectroscopy, photoluminescence spectroscopy (PL), and X-ray diffraction (XRD). The effect of precursor concentration on the morphology and size of the nanoparticles was investigated. It was observed that an increase in the precursor concentration resulted in an increase in particle sizes with different morphologies for both Ag and Cu nanoparticles. The increase in particle sizes for Ag nanoparticles was due to Ostwald ripening, while for Cu nanoparticles it was due to agglomeration, as Cu tends to oxidize in the atmosphere, leading to a change in particle size and shape. However, the ability to control and manipulate their physical and chemical properties depends on tuning their size and shape. Therefore, varying the precursor concentration helped in selecting the optimal concentration for this study. The nanoparticles produced were used in another study as fillers or additives for the production of nanofiber composites. The development of nanofibers by electrospinning process has led to potential applications in filtration, tissue engineering scaffolds, drug delivery, wound dressing and etc. The current study is an attempt to fabricate composite nanofibers that can be used as wound dressing material for effective wound healing. The approach involves the blending of two different polymers both being biocompatible and biodegradable were one is a natural polymer and the other is a synthetic polymer. In this study, different weight ratios of CS/PVA blends, Ag/Cu/CS/PVA, Ag/CS/PVA and Cu/CS/PVA composite fibers have been successfully prepared by the electrospinning process. The tip-to-collector distance was kept at 15 cm and the applied voltage was varied from 15 to 25 kV. The effects of the weight ratios applied voltage and the nanoparticles loading on the morphology and diameter of the fibers were investigated. The resultant fibers were characterized using scanning electron microscopy (SEM), XRD, Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA) and UV-Vis spectroscopy. The SEM results showed that an increase the amount of chitosan in the CS/PVA blend resulted in a decrease in the fiber diameters while an increase in the voltage from 15 to 25 kV led to a decrease in the fiber diameters. Furthermore, an increase in fiber diameters was observed with irregular morphologies upon addition of Ag/Cu nanoparticles into the blend. The latter changes are perceived to be as a result of an increased conductivity and a higher charge density. The XRD results showed peaks which correspond to Ag in the face centred cubic. Ag peaks are more dominant than Cu peaks in the XRD of the mixed nanoparticles. The FTIR spectra of the Ag/Cu/CS/PVA composite fibers gave almost identical features as the blend. This proves that there was an interaction between CS and PVA polymer due to intermolecular hydrogen bonding. The TGA curves showed no significant effect on the thermal stability of the composite fibers upon addition of different nanoparticles loadings. The absorption spectra of the composite fibers showed an improved optical properties compared to the blend. For Ag and Cu nanoparticles composite fibers it was observed that addition of Ag nanoparticles in the blend resulted in an increase in fiber diameters with uniform morphology whereas for Cu resulted in a decrease in fiber diameters. Both Ag and Cu composite fibers showed an improved optical properties. The effect of CS/PVA, Ag/Cu, Ag, and Cu nanofibers on the selected microorganism (K.pneumoniae, S. aureus, P. aeruginosa, and E.coli) was evaluated using the disk diffusion method. It was observed that Ag/Cu/CS/PVA composite fibers showed greater activity against all microorganisms compared to Ag and Cu composite fibers. The alamar blue and Pierce Lactase dehydrogenase (LDH) assay were used to assess the effect of the blend and the composite fibers on cell viability and cytotoxicity, respectively. The results show that the prepared blend and the composite fibers did not have any toxic effect on human adipose derived stem cells (hADSC). The results also showed that as the concentration of Ag/Cu nanoparticles was increased the viability of the cells also increased after 24 hour incubation. More proliferation was observed in day 1 compared to day 3. The 30/70 blend showed more viable cell compared to the negative control. For Ag and Cu composite fibers the 30/70 CS/PVA blend increased cell proliferation after 3 days with 17% more viable cells compared to the negative control. These results show that the prepared blend with its composite fibers are biocompatible with human (ADSC) and may be suitable for use in biomedical application such as wound dressing.
D. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Polymeric composite nanofiber; Antibacterial activities; Wound healing; Transmission electron microscopy (TEM); Silver and copper nanoparticles; Synthesis; Polymers; Chitosan nanofibers; Composite fibers; Antimicrobial activity; Chronic wounds; Wound inflammation, proliferation, and maturation; Nanofiber scaffolds; Dissertations, Academic -- South Africa.; Nanostructured materials.; Wound healing.; Polymers.; Nanofibers.